Effectiveness of ESG practices in enhancing firm value: Evidence from Indonesian banking - Sari, Delina Dwi Indah; Valdiansyah, Riyan Harbi (Journal of Contemporary Accounting, 2025)
This study uses profitability (ROA) as a moderating variable to examine how Environmental, Social, and Governance (ESG) affects the firm value of Indonesian banking firms. Secondary data were obtained from 121 observations of banks listed on the Indonesia Stock Exchange during 2018–2023, covering the pre, during, and post COVID-19 periods. ESG performance was measured using the Bumi Global Karbon (BGK) Foundation score, while Tobin's Q ratio was used to calculate firm value. Panel data regression with a Fixed Effect Model under the Moderated Regression Analysis (MRA) approach was employed. The results show that ESG has a negative effect on firm value, while the ESG ROA interaction has a significantly positive effect, indicating that profitability strengthens ESG’s contribution to firm value. Control variables, leverage, and firm size were found insignificant. The findings highlight the need for financial readiness before intensive ESG adoption and the importance of regulatory incentives to promote ESG implementation without reducing profitability.